Non‐enzymatic cross‐linking of collagen type II fibrils is tuned via osmolality switch. Issue 7 (13th February 2018) - Pouran, Behdad; Moshtagh, Parisa R.; Arbabi, Vahid; Snabel, Jessica; Stoop, Reinout; Ruberti, Jeffrey; Malda, Jos; Zadpoor, Amir A.; Weinans, Harrie
ABSTRACT: An important aspect in cartilage ageing is accumulation of advanced glycation end products (AGEs) after exposure to sugars. Advanced glycation results in cross‐links formation between the collagen fibrils in articular cartilage, hampering their flexibility and making cartilage more brittle. In the current study, we investigate whether collagen cross‐linking after exposure to sugars depends on the stretching condition of the collagen fibrils. Healthy equine cartilage specimens were exposed tol ‐threose sugar and placed in hypo‐, iso‐, or hyper‐osmolal conditions that expanded or shrank the tissue and changed the 3D conformation of collagen fibrils. We applied micro‐indentation tests, contrast enhanced micro‐computed tomography, biochemical measurement of pentosidine cross‐links, and cartilage surface color analysis to assess the effects of advanced glycation cross‐linking under these different conditions. Swelling of extracellular matrix due to hypo‐osmolality made cartilage less susceptible to advanced glycation, namely, the increase in effective Young's modulus was approximately 80% lower in hypo‐osmolality compared to hyper‐osmolality and pentosidine content per collagen was 47% lower. These results indicate that healthy levels of glycosaminoglycans not only keep cartilage stiffness at appropriate levels by swelling and pre‐stressed collagen fibrils, but also protect collagen fibrils from adverse effects of advanced glycation. These findings highlight the fact that collagen fibrils and therefore cartilage can be protected from further advanced glycation ("ageing") by maintaining the joint environment at sufficiently low osmolality. Understanding of mechanochemistry of collagen fibrils provided here might evoke potential ageing prohibiting strategies against cartilage deterioration. © 2018 The Authors. Journal of Orthopaedic Research Published by Wiley Periodicals, Inc. on behalf of Orthopaedic Research Society. J Orthop Res 36:1929–1936, 2018.